2020
DOI: 10.3390/nu12020567
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Mediterranean Diet Related with Physical Fitness and Physical Activity in Schoolchildren Aged 6–13

Abstract: The relationship between adherence to the Mediterranean Diet (MD) and both physical fitness (PF) and physical activity (PA) level has been analysed in several studies. The aim of this research was to describe, compare and analyse the level of PF and PA in schoolchildren aged 6–13 in the Region of Murcia, according to adherence to the MD. A descriptive and cross-sectional study was performed. A total of 370 schoolchildren (44.9% girls) aged 6–13 (8.7 ± 1.8) from six primary schools in the Region of Murcia (Spai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 47 publications
1
31
1
Order By: Relevance
“…However, there were no significant differences in the BMI or any of the other anthropometric measures. These results are consistent with those previously reported by other studies (Jaakkola et al, 2015;Fang et al, 2017;Fernández-Bustos et al, 2019;López-Gil et al, 2020). Conversely, no significant differences were observed between genders when comparing PA levels, which is not in accordance with previous research studies where evidences of higher PA practice levels for boys were reported (Owen et al, 2009;Riddoch et al, 2009;Collings et al, 2013;Griffiths et al, 2013;Voss et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…However, there were no significant differences in the BMI or any of the other anthropometric measures. These results are consistent with those previously reported by other studies (Jaakkola et al, 2015;Fang et al, 2017;Fernández-Bustos et al, 2019;López-Gil et al, 2020). Conversely, no significant differences were observed between genders when comparing PA levels, which is not in accordance with previous research studies where evidences of higher PA practice levels for boys were reported (Owen et al, 2009;Riddoch et al, 2009;Collings et al, 2013;Griffiths et al, 2013;Voss et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…When the subject did not reach the end line twice following the acoustic signal or stopped completely due to the fatigue, the test was finished. Léger's et al (1988) equations were used in order to transform the states to relative MOC values (López-Gil et al, 2020).…”
Section: Cardiorespiratory Fitness (Crf)mentioning
confidence: 99%
See 3 more Smart Citations